Politicization of Religion: Religion in Political Discourse - Fajar Syarif (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
This article discusses the position of religion in politics that has relation to leadership. The main argumentation of this research is religion will constantly become a political power and social movement. In one side the research has a different opinion from the integration politic paradigm and secular that proposed by Hasan al-Bannā and ‘Alī Abd. al-Rāziq, but in other side, it has reinforced the two paradigms. By using literature study and descriptive method and philosophical historical approach, it indicates Islam will constantly exist and has influence in the political process. Although Islam is not depending on politics and on the contrary. Islam and politic are both integrated dimensions of life, so both are not able to be separated from social political dynamics.